Thermal and Spectroscopic Dynamics of Titanium Oxide Functionalized Polyaniline Coated Sawdust - Matoetoe, Mangaka; Okumu, Fredrick; Maphale, Connie; Fatoki, Olalekan (Asian Journal of Chemistry, 2015)
Natural cellulose (sawdust) usage is limited by its poor physical and chemical properties. This study looks into the effects of chemical treatment of sawdust with polyaniline. Polyaniline (PANI) was chemically polymerized in situ from aniline in acid medium containing sawdust and/or titanium oxide (TiO2) to form polyaniline composites (PANI/SD, PANI/SD/TiO2 and PANI/SD/TiO2). These composites spectrophotometric, structural, morphological and thermal properties were determined using various spectrophotometric techniques such as fourier transform infrared (FTIR), UV-visible, transmission electron microscope (TEM), thermogravimetric (TG) and differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD). Results indicate structure retention by the polyaniline, Sawdust and titanium oxide. However, minor chemical shifts were indicative of a physio-chemical interaction between the functional groups. The marked morphological changes observed from the pure chemicals and composites suggests multi-layer formation. Thermal studies showed two weight loss waves; 1st waves are due to water and doping material loss while 2nd wave losses are a result of polymer decomposition. The weight loss trend was: PANI/SD < PANI < PANI/SD/TiO2 < PANI/TiO2, thus suggesting a thermal stability improvement with the addition of TiO2. Powder X-ray diffraction confirmed the structural retention of pure polyaniline and sawdust as indicated by the appearance of their representative broad 2q angles at 20°, 26° and 15°, 24°.